2011
DOI: 10.1007/s11032-011-9579-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity arrays technology (DArT) markers in apple for genetic linkage maps

Abstract: Diversity Arrays Technology (DArT) provides a high-throughput whole-genome genotyping platform for the detection and scoring of hundreds of polymorphic loci without any need for prior sequence information. The work presented here details the development and performance of a DArT genotyping array for apple. This is the first paper on DArT in horticultural trees. Genetic mapping of DArT markers in two mapping populations and their integration with other marker types showed that DArT is a powerful high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…The average sequence length of a rye DArT marker (508 bp) is within range of those reported for other species: Sugarcane – 465 bp (Aitken et al, 2014), oats – 496 bp (Tinker et al, 2009), Eucalyptus – 534 bp (Petroli et al, 2012) and similarly like in other studies, in which such data was reported (Tinker et al, 2009; Schouten et al, 2012), the majority of contigs obtained after redundancy analyzes consisted of two or three sequences. On the other hand, the sequence redundancy (39.5%) was generally slightly higher than in other species – the redundancy estimates were 31.22%, 32.73% and between 33.75 and 44.14% for sugarcane, oats, and Eucalyptus , respectively (Tinker et al, 2009; Petroli et al, 2012; Aitken et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The average sequence length of a rye DArT marker (508 bp) is within range of those reported for other species: Sugarcane – 465 bp (Aitken et al, 2014), oats – 496 bp (Tinker et al, 2009), Eucalyptus – 534 bp (Petroli et al, 2012) and similarly like in other studies, in which such data was reported (Tinker et al, 2009; Schouten et al, 2012), the majority of contigs obtained after redundancy analyzes consisted of two or three sequences. On the other hand, the sequence redundancy (39.5%) was generally slightly higher than in other species – the redundancy estimates were 31.22%, 32.73% and between 33.75 and 44.14% for sugarcane, oats, and Eucalyptus , respectively (Tinker et al, 2009; Petroli et al, 2012; Aitken et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…To date sequence information was obtained for sets of selected DArT markers from a few genotyping panels. The species in question include Eucalyptus (Petroli et al, 2012), oats (Tinker et al, 2009), sugarcane (Aitken et al, 2014), wheat (Marone et al, 2012), apple (Schouten et al, 2012), and potato (Traini et al, 2013). This is the first report concerning rye DArT marker sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The peak of the major QTL of Ma was initially located between markers CH02a03 and CH05c06 in PI 613988, and later was confirmed with the fine map of the Ma locus in Royal Gala, PI 613988 and PI 613971. The CH02a03-CH05c06 interval was best compared with the interval between markers CH05e04z and CH05c06 in Telamon where a major fruit acidity QTL was detected, although the same interval was inverted in Braeburn (Kenis et al 2008;Schouten et al 2011). Except for the Ma locus, there were no common QTL detected for fruit acidity among the crosses studied to date.…”
Section: Marker-assisted Breeding For Fruit Aciditymentioning
confidence: 83%
“…The Ma gene has been mapped to the proximal end of linkage group (LG) 16 between the simple sequence repeat (SSR) markers CH02a03 and CH05e04 in a presumably Mama 9 Mama cross (Prima 9 Fiesta) (Maliepaard et al 1998;Schouten et al 2011). In these studies, fruit acidity was evaluated with pH indicator paper and the progeny were classified into two categories of three genotypes based on fruit pH, i.e., MaMa/Mama (pH \ 3.8) and mama (pH [ 3.8).…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of the mapping technology resulted in maps for many other cultivars including: 'Wijcik McIntosh' (WM), NY 75441-67, NY 75441-58, 'Telamon', 'Braeburn', 'Prima', 'Fiesta', 'Discovery', 'Ralls Janet', 'Delicious', covering from 842 cM (Conner et al 1997, Maliepaard et al 1998, Kenis & Keulemans 2005, Igarashi et al 2008 to almost 2000 cM in integrated maps (N'Diaye et al 2008. The maps were constructed and saturated using RAPD (Random Amplified Polymorphic DNA), RFLP (Restriction Fragment Length Polymorphism), AFLP (Amplified Fragment Length Polymorphism) (Hemmat et al 1994, Maliepaard et al 1998, Liebhard et al 2002, 2003, and more recently SSR (Simple Sequence Repeat), SNP (Single Nucleotide Polymorphism) (Silfverberg-Dilworth et al 2006, Igarashi et al 2008, cDNA microarray (Soglio et al 2009) and diversity array technology (DArT) based markers (Schouten et al 2012). Among them many sequences were linked to economically important traits such as plant resistance to pests and diseases, plant growth habit, fruit colour, acidity and sweet taste (Korban & Tartarini 2009).…”
Section: Introductionmentioning
confidence: 99%